Assessing the environmental sustainability of insects as a source of functional proteins: A prospective LCA - Alejandro Corona-Mariscal; Neus Sanjuan; Carme Güell; Gabriela Clemente (Future Foods)
Summary: Insect protein has properties that enable its use as a functional ingredient in food and feed formulations. This study provides a prospective life cycle assessment (LCA) of proteins of Alphitobius diaperinus from an upscaling of a lab-scale process. The functional unit is 1 kg protein, and the system boundaries are from the cradle to the processing gate. As the process yields fat as a coproduct, avoided loads and physicochemical allocation are applied. Different results are obtained regardless of how coproducts are dealt with; protein extraction is the unit process that contributes the most to the processing stage. Compared with whey protein isolate, the impacts of A. diaperinus are lower in five of six categories using allocation but only in three categories using avoided loads. This study highlights that the multifunctionality of food systems is crucial in determining the product's impacts, being also critical for comparison purposes.